Investigating the Dynamic Link between External Reserves and Monetary Variables in Nigeria - Chile, Nzeh, Innocent; Onyeanuna, Ahamba, Kenneth; Eze, Millicent Adanne; Jane, Akaolisa, Chidiogo; Edith, Nkamnebe, Ogochukwu (Growth, 2021)
Nigeria is a country whose revenue base is woven around the oil sector. Consequently, any shock to the international price of oil definitely affects the reserve position of the country. Our major motivation for this study is therefore anchored on the volatile nature of the country’s reserves and how domestic monetary variables respond to shocks in the external reserves as well as possible reverse responses of external reserves to changes in monetary variables. Using monthly series over a period of 2007-2019 and under the framework of the VAR, our findings revealed a dynamic relationship that exists between external reserves and monetary variables in Nigeria. That is, as monetary variables responded to shocks in external reserves, a reverse response was also noticed running from external reserves to changes in monetary variables. The impact of oil to the economy was exhibited in the result as external reserves responded positively to oil price shocks; thus showing the importance of the oil sector to the country’s reserve position. We therefore recommend that a synergy should exist between monetary and fiscal authorities in order to neutralize the destabilizing effect of unsustainable increase in reserve inflows and to diversify the economy away from the oil sector to reduce volatility in reserves inflows.